Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1002/jnr.20494
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of bone marrow stromal cell transplantation in injured rodent brain: Synthesis of neurotrophic factors

Abstract: Several groups have suggested that transplantation of marrow stromal cells (MSCs) promotes functional recovery in animal models of brain trauma. Recent studies indicate that tissue replacement by this method may not be the main source of therapeutic benefit, as transplanted MSCs have only limited ability to replace injured central nervous system (CNS) tissue. To gain insight into the mechanisms responsible for such effects, we systematically investigated the therapeutic potential of MSCs for treatment of brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(109 citation statements)
references
References 46 publications
(56 reference statements)
3
101
1
2
Order By: Relevance
“…43 The potentially important role of induction of local neurotrophic factors is also supported by Chen et al, 44 who showed that intraventricular injection of MSCs in a murine model resulted in an increase in NGF levels as measured in the cerebrospinal fluid. Other mechanisms have been suggested to explain the action of transplanted MSCs, such as an elevated level of transforming growth factor-b (TGF-b) that helps to reduce the formation of scar tissue, and restoration of cerebral blood flow and the blood-brain barrier in models of traumatic brain injury 45 and stroke.…”
Section: Nonhuman Mscsmentioning
confidence: 87%
“…43 The potentially important role of induction of local neurotrophic factors is also supported by Chen et al, 44 who showed that intraventricular injection of MSCs in a murine model resulted in an increase in NGF levels as measured in the cerebrospinal fluid. Other mechanisms have been suggested to explain the action of transplanted MSCs, such as an elevated level of transforming growth factor-b (TGF-b) that helps to reduce the formation of scar tissue, and restoration of cerebral blood flow and the blood-brain barrier in models of traumatic brain injury 45 and stroke.…”
Section: Nonhuman Mscsmentioning
confidence: 87%
“…injury [165,[169][170][171][172] and potentially in clinical settings [173,174]. However, previous studies show that only a small proportion of transplanted MSCs actually survive and few MSCs differentiate into neural cells in injured brain tissues.…”
Section: Neuroprotective and Neurorestorative Processes In The Traumamentioning
confidence: 99%
“…BMCs grafting on SCI injury models have been studied and it has been observed that the transplanted BMCs improve neurological deficits by generating myelin producing cells or neural cells [117,118] . Furthermore, BMCs can produce neuroprotective cytokines, rescuing the neurons with impending cell death in case of injury [119,120] . Also, several clinical trials have explored the hypothesis that cell transplantation may enhance the recovery of neurological functions after SCI.…”
Section: Bone Marrow Cellsmentioning
confidence: 99%